Drug abuse –a depressed economy and a young Nigerian generation on the hook - Jasper, Abiodun Oyinpreye; Edafiadhe, Wilson; Jasper, Gladys Chidinma (International Journal of Psychosocial Rehabilitation, 2020)
The first report of drug abuse in Nigeria was made in 1940s, after the Second World War, when the use of cannabis, pethidine, phenobarbit one and amphetamine were observed. Studies done by UNDP in 4 geographical zones in 1998 and 1999 showed that drug abuse was an emerging and growing problem among Nigerian youths with cannabis being the most predominantly used irrespective of the section of the country. Newer drugs of abuse are daily coming on board. Discussion With poverty and unemployment indices rising especially among youths, drug use seems to be on the increase. Global Price of crude oil which is Nigeria’s major source of income, has also taken a downward turn in recent years; made worse by the recent Corona virus pandemic. Crime rate is also on the increase; as poverty and crime seem to be inseparable Siamese twins. Despite concerted (Local and international) efforts by WHO, UNODC, NAFDAC and NDLEA over the years, Drugs are becoming more easily accessible and are being used by an increasing number of Nigerian youths. Summary Though drug abuse is fast becoming a global epidemic the Nigerian situation needs urgent attention; fuelled by poverty, unemployment and easy access to illicit drugs and medically un- prescribed drugs. Access to uncensored information via the internet, strong desire to explore and compete among peers are other issues accelerating this trend. This is taking an alarming dimension among youths in Nigeria that constitute a predominant proportion of the over 200 million population of the country with over 50% unemployment rate. This is a whole generation on the hook. Efforts to reverse this trend must not only be global, but long lasting efforts and structures must be domiciled in Nigeria to save this young generation from this catastrophe.